Les ouvrages de franchissement des aqueducs antiques de Bourges - Marianne Surgent (Revue Archéologique du Centre de la France)
Since a study begun in 2007 on hydraulics in ancient berry (financed by DRAC du Centre), about twenty works of engineering were listed on two of the four aqueducts feeding the county seat of city (Avaricum). It’s essentially about seven bearing walls and ten tunnels for the aqueduct of Traslay; of a bearing wall and a bridge or bridge-siphon for the aqueduct of Menetou-Salon. They are all not represented by vestiges still of rise. An abundant documentation old and resulting from recent archaeological excavations testifies nevertheless to their presence and illustrates their modes of construction. These works attest deeply underground and air advance aqueducts, in a little marked topographic context. This article comes in complement from data published recently, on the installations of collecting of the aqueducts and the petroarcheological study of the mortars of the aqueduct of Traslay.